Gravidez nas adolescências : construções das identidades ocupacionais maternas durante a gestação - Martins, Sofia (2017)
Introduction: The World Health Organization defines adolescence, chronologically, as an age group between 10 and 19 years. In this work, a perspective of the term’s plurality is adopted, since adolescents are shaped by concrete conditions of life and trajectories, with the purpose of defending the development of adolescents’ potentials. Studies on teenage pregnancy have reported diverging views of gestation and of motherhood. In this sense, we verified the need to broaden the understanding of the diversity and uniqueness that encompasses this phenomenon through the lenses of occupational therapy, investigating from the conceptual framework of the occupational identity. Objective: to understand how adolescent pregnant women construct maternal occupational identities. Method: applied field research using exploratory qualitative methods, undertaken in five Health Units of a municipality of São Paulo state. The study included 10 adolescent pregnant women, three of them in the first trimester of gestation, two in the second and five in the third. The study took place in two stages: 1) obtaining sociodemographic and occupational data; 2) understanding the process of construction of the maternal occupational identity. Instruments for data collection: Brazilian Sociodemographic Classification Criterion – Abep; occupational journal linked to occupational inquiry list; and semi-structured interview script. For the analysis, we categorized and presented data of the first stage descriptively and those of the second stage through Collective Subject Discourse Methodology (DSC). Results: the results were organized in three dimensions: general characterization of the participants; the process of discovering pregnancy; the process of constructing the maternal occupational identity. Dimension I shows that the age of participants varies between 14 and 19 years and most of them are of low-middle class. None of them wanted to get pregnant at this point in their lives. Dimension II shows different positions and opinions in face of the discovery of a pregnancy, which demonstrates the plurality and the individuality of the representation of this phenomenon. The main source of support for adolescents is family. Dimension III reflects on the construction of the maternal occupational identity, identifying activities performed before gestation that may help in the future care of the baby as well as revealing activities performed during gestation that characterize occupational changes related to the care of the woman herself alongside the baby’s care. Discussion: knowing the life history of pregnant adolescent women as well as explaining the creation and construction of occupational identities allows ponderation on the plurality of perceptions about pregnancy and accessing what makes sense to them. Daily occupational choices express who they want to become and how they would like others to see them. Final considerations: the study contributes to ponder the integral health care of pregnant adolescents parting from their context, providing answers to their needs and providing subsidies for the planning of intersectorial actions and strategies that promote youth participation and protagonism. This perspective expands development of the adolescent’s autonomy for self-care and childcare and the process of constructing the maternal occupational identity.